Parasitoid Hama Penggerek Batang dan Pucuk Tebu di Cinta Manis, Ogan Ilir Sumatera Selatan - Dewi Meidalima (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2014)
Serangan hama penggerek tebu siap panen sebesar 11,25% di Cinta Manis tahun 2007. Lahan pengamatan 1 ha di bagi menjadi 5 petak secara diagonal, masing-masing seluas 200 m2, populasi tanaman sebanyak 1500 batang. Tujuan penelitian mengetahui keanekaragaman, spesies parasitoid dan potensi parasitasinya. Ditemukan 3 spesies parasitoid telur (Trichogramma chilonis; Telenomus dignoides; Tetrastichus schoenobii) dan 3 spesies parasitoid larva (Rachonathus scirpophagae; Stenobracon nicevillei; Diatraeophaga striatalis). Parasitisasi parasitoid telur penggerek pucuk di lahan dengan dan tanpa tumbuhan liar oleh Telenomus dignoides, Tetrastichus schoenobii, Trichogramma chilonis sebesar 6,96% dan 80,48%; 29,13% dan 15,22%; 0% dan 0,71%. Parasitisasi parasitoid telur penggerek batang di lahan dengan dan tanpa tumbuhan liar oleh Tetrastichus schoenobii sebesar 48,88% dan 36,08%, Telenomus dignoides sebesar 29,35% dan 28,34%. Parasitisasi parasitoid larva penggerek pucuk di lahan dengan dan tanpa tumbuhan liar oleh Rachonothus scirpophagae sebesar 2,66% dan 1,59%, dan Stenobracon nicevillei sebesar 1,81% dan 0,99%. Parasitisasi parasitoid larva penggerek batang (Diatraeophaga striatalis), di lahan dengan dan tanpa tumbuhan liar sebesar 32,23% dan 19,62%. Keanekaragaman spesies parasitoid telur (H’=0,627)dan larva penggerek pucuk (H’=0,686) tertinggi pada lahan dengan tumbuhan liar. Keanekaragaman spesies parasitoid telur penggerek batang tertinggi pada lahan tanpa tumbuhan liar adalah H’=0,686. During 2007 in Cinta Manis area, the attack of borers on readily harvested sugarcane reached 11.25%. A 1-ha observation field was divided diagonally into 5 plots, each with an area of 200 m2, and populated with 1,500 plants. The aims of this study were to know the diversity of parasitoids species and their parasitic potentials. As many as 3 species of parasitoid eggs (Trichogramma chilonis; Telenomus dignoides; Tetrastichus schoenobii) and 3 species of parasitoid larvae (Rachonathus scirpophagae; Stenobracon nicevillei; Diatraeophaga striatalis) have been found. The parasitization of shoot borer egg parasitoids (Telenomus dignoides, Tetrastichus schoenobii, Trichogramma chilonis) in the field with and without wild plants were 61.96% and 80.48%; 29.13% and 15.22%; 0% and 0.71%, respectively. The parasitization of stem borer egg parasitoids of Tetrastichus schoenobii in the field with and without wild plants were 48.88% and 36.08%, respectively, and of Telenomus dignoides were 29.35% and 28.34%, respectively. The parasitization of shoots borer larval parasitoids of Rachonothus scirpophagae in the field with and without wild plants were 2.66% and 1.59%, respectively, and of Stenobracon nicevillei were 1.81% and 0.99%, respectively. Parasitization of larvae parasitoid stem borer (Diatraeophaga striatalis) in the field with and without the wild plants were 32.23% and 19.62%, respectively. The highest diversity of eggs (H’=0.627) and larvae (H’=0.686) of shoot borer parasitoid species were in the field with wild plants. The highest diversity of egg stem borer parasitoid species in the field without wild plants was H’=0.686.